The expectations of Finnish RE student teachers of their professional development in their academic studies in the light of twenty-first-century skills. Issue 4 (2nd October 2019) - Viinikka, Kaisa; Ubani, Martin
ABSTRACT: This study examines what kind of expectations religious education (RE) student teachers have about their professional development during their academic studies. The study focuses on eight RE student teachers in teacher education in Finland. The students were studied in light of the twenty-first-century skills framework. The analysis was deductive content analysis with quantification of the results. There were several results from the study. For instance, much of the learning expectations of the student teachers were connected to the perceived tasks of the RE teacher. The RE student teachers also considered the twenty-first-century skills as relevant for a competent RE teacher in future. The student teachers expected to gain competence in religious literacy and dialogue skills from the theological studies. The participants seemed to emphasise the acquisition of social and interaction skills but also dialogue skills from the pedagogical studies.